The relationship between screen time, screen content for children aged 1-3, and the risk of ADHD in preschools - Jian-Bo Wu; Yanni Yang; Qiang Zhou; Jiemin Li; Wei-Kang Yang; Xiaona Yin; Shuang-Yan Qiu; Jingyu Zhang; Minghui Meng; Yawei Guo; Jian-hui Chen; Zhaodi Chen (PLoS ONE, 2025)
Objective This study investigates the relationship between screen time, screen content, and the risk of Attention Deficit Hyperactivity Disorder (ADHD) using data from a large sample. Specifically, it examines how different types of screen content (such as educational videos, cartoon videos, and interactive videos) are associated with the risk of ADHD. The aim is to offer a scientific foundation for the rational management of children’s screen time and screen content. Methods We collected data through a questionnaire survey involving a study population of 41,494 children from Longhua District, Shenzhen City, China. The questionnaire recorded the daily screen time and the type of content viewed by the children at ages 1–3 years and assessed their risk of ADHD using the Strengths and Difficulties Questionnaire (SDQ) at ages 4–6 years. Hierarchical logistic regression analysis, controlling for confounding factors, was employed to explore the associations between screen time, screen content, and ADHD risk. Results In the total sample, 6.7% of the participants had screen time exceeding 60 minutes per day, with educational videos predominant type (63.4%). 16.5% of the participants were identified as being at risk for ADHD. Statistically significant positive associations with ADHD were observed across all categories of screen time (P<0.001). Moreover, as screen time increased, the risk of ADHD also rose (OR1~60 mins/d=1.627, 95%CI=1.460~1.813; OR61~120 mins/d=2.838, 95%CI=2.469~3.261; OR>120 mins/d=3.687, 95%CI=2.835~4.796). Significant positive associations with ADHD were observed across all categories of screen time in the educational videos and cartoon videos. For the educational videos group, the odds ratios were as follows: OR1–60 mins/day=1.683 (95% CI=1.481–1.913), OR61–120 mins/day=3.193 (95% CI=2.658–3.835), and OR>120 mins/day=3.070 (95% CI=2.017–4.673). For the cartoon videos group, the odds ratios were: OR1–60 mins/day=1.603 (95% CI=1.290–1.991), OR61–120 mins/day=2.758 (95% CI=2.156–3.529), and OR>120 mins/day=4.097 (95% CI=2.760–6.081). However, no significant associations with ADHD risk were found for any category of screen time in the interactive videos group (OR1~60 mins/d=0.744, 95%CI=0.361~1.534; OR61~120 mins/d=0.680, 95%CI=0.296~1.560; OR>120 mins/d=1.678, 95%CI=0.593~4.748). Conclusion Increased screen time is associated with a higher risk of ADHD, particularly for educational and cartoon videos, while interactive videos show no significant link. To mitigate this risk, parents and educators should implement strategies such as setting time limits, encouraging breaks, and promoting alternative activities. Future research should focus on longitudinal studies and intervention trials to further explore and address this relationship.